Introduction to Philosophy Epistemology - Barnett, Brian C.; Hendricks, Christina (Open textbook library., 2021)
Introduction to Philosophy: Epistemology engages first-time philosophy readers on a guided tour through the core concepts, questions, methods, arguments, and theories of epistemology—the branch of philosophy devoted to the study of knowledge. The book progresses systematically while placing key ideas and thinkers in historical and contemporary context. Central topics include the analysis of knowledge, the nature of epistemic justification, rationalism vs. empiricism, skepticism, the value of knowledge, the ethics of belief, Bayesian epistemology, social epistemology, and feminist epistemologies.